MODEL STRATEJIK PENGEMBANGAN USAHA KECIL PERKOTAAN (Kasus pada Usaha Mikro dan Kecil Pangan di Kota Palembang) - M. Syahirman Yusi (Politeknik Negeri Sriwijaya, 2014)
This study was intended to formulate the model of micro and small scale of food enterprise in Palembang by determining both the level and the influencing factors business climate, development and training, business technology, competitive advantage strategy, business self reliance, business progress, and business continuity. Survey and interview technique were implemented among 100 samples. Data was analyzed by using both one way anova test and structural equation modeling. The result indicated that business climate, development and training, business technology had a positive influence toward the competitive advantage strategy and business self reliance. Competitive advantage strategy had a positive influence toward the business self reliance and business progress, and business progress had a positive influence toward the business continuity. Those above results analysis indicated that all of the proposed research hypothesis and theoretical model were not rejected.